Comparative experiment of various irrigation technologies in maize (Zea mays L.) - Bencze, Gábor; Komlósi, Ádám; Futó, Zoltán (COLUMELLA – Journal of Agricultural and Environmental Sciences, 2022)
Development of domestic maize cultivation largely depends on the applied agrotechnics. In keeping the increase in crop increases, the goal is to minimize crop fluctuations, and there is also an important role in the proper water supply. In our country, the yield of maize is a good water supply. The yield of maize can be significantly increased by improving the water supply of the plant. In many areas there are only very few water available for professional irrigation, so it is increasingly need to focus on modern, most water-saving irrigation technologies. In our experiment, we compare two irrigation techniques. The rain-like watering with console and the solenoid valve-controlled tape drip irrigation. Our examinations extend to mapping the properties of maize that can cause changes in the effect of irrigation and, of course, to develop crop quantities available by various irrigation technologies, since these results provide the proper income for the producer. The research was carried in Szarvas, at the school experimental field of the Hungarian University of Agriculture and Life Sciences, Department of Irrigation and Melioration, in 2020.